Controls on Holocene denudation rates in mountainous environments under Mediterranean climate. Issue 2 (28th July 2016) - Molliex, S.; Jouet, G.; Freslon, N.; Bourlès, D. L.; Authemayou, C.; Moreau, J.; Rabineau, M.
Abstract: The Mediterranean domain is characterized by a specific climate resulting from the close interplay between atmospheric and marine processes and strongly differentiated regional topographies. Corsica Island, a mountainous area located in the western part of the Mediterranean Sea is particularly suitable to quantify regional denudation rates in the framework of a source‐to‐sink approach. Indeed, fluvial sedimentation in East‐Corsica margin is almost exclusively limited to its alluvial plain and offshore domain and its basement is mainly constituted of quartz‐rich crystalline rocks allowing cosmogenic nuclide 10 Be measurements. In this paper, Holocene denudation rates of catchments from the eastern part of the island of Corsica are quantified relying on in situ produced 10 Be concentrations in stream sediments and interpreted in an approach including quantitative geomorphology, rock strength measurement (with a Schmidt Hammer) and vegetation cover distribution. Calculated denudation rates range from 15 to 95 mm ka ‐1 . When compared with rates from similar geomorphic domains experiencing a different climate setting, such as the foreland of the northern European Alps, they appear quite low and temporally stable. At the first order, they better correlate with rock strength and vegetation cover than with morphometric indexes. Spatial distribution of the vegetation is controlled by morpho‐climatic parameters including sun exposure and the direction of the main wet wind, so‐called 'Libecciu'. This distribution, as well as the basement rock strength seems to play a significant role in the denudation distribution. We thus suggest that the landscape reached a geomorphic steady‐state due to the specific Mediterranean climate and that Holocene denudation rates are mainly sustained by weathering processes, through the amount of regolith formation, rather than being transport‐limited. Al/K measurements used as a proxy to infer present‐day catchment‐wide chemical weathering patterns might support this assumption. Copyright © 2016 John Wiley & Sons, Ltd.